UniSky, lo spin-off dello IUAV per il monitoraggio del territorio e dell’ambiente - Di Prinzio, Luigi; Giannotti, Vincenzo; Borga, Giovanni; Picchio, Stefano (GEOmedia, 2010)
Unisky, the University of Venice spin-off Unisky is a recently born spin-off of the University of Venice (IUAV). The exeperiences and skills of the envolved researchers, coming from different academic departments, led to the institution of this modern working group, which is mainly focused in providing sistemic and permanent monitoring of land and environment. The projects carried out by Unisky favoured a strong partnership network with private companies, able to complete the spin-off technological offer.